REVIEW ON THE IMPLEMENTATION OF PARTICLE SWARM OPTIMIZATION TECHNIQUE IN SOLVING THE HYDROTHERMAL SCHEDULING - Zaheer, S.; Haroon, S.; Malik, T. N.; Hashmi, I. (The Nucleus, 2013)
Short term hydrothermal scheduling (STHTS) is a very complex, dynamic large-scale non-linear optimization problem. There are many algorithms and powerful optimization methods used to address this issue. Evolutionary algorithms have been effectively employed to obtain a global optimized solution of non linear problems like STHTS. Particle Swarm Optimization (PSO) is an evolutionary method. It can be successfully employed to get a best possible solution of STHTS problem due to its features of robustness, easy implementation and computational efficiency. Here the literature on the Particle Swarm Optimization method is collected and reviewed to sort out the STHTS problem. A review of most of the publications upto 2012 on this topic is given.